Experimentation Abilities in Kindergarten Children with Learning Problems - Joep van der Graaf; Eliane Segers; Ludo Verhoeven (Lectito Journals, 2018)
In the present study we investigated experimentation abilities of children with learning problems in early childhood education, i.e. kindergarten (4-6 years old). An essential part of science education is learning via the scientific method, of which experimentation is the central component. We studied experimentation abilities in 28 kindergartners with mild learning problems and compared them to 45 grade-matched typically developing kindergartners. Moreover, it was examined to what extent linguistic and cognitive factors in experimentation could be identified. The results showed that the kindergartners with learning problems scored lower on experimentation, which was due to the difficulty they experienced when the number of variables increased. There was an overlap in performance of kindergartners with and without learning problems, which showed that some kindergartners with learning problems performed similar to typically developing kindergartners on the experimentation task. Similar cognitive and linguistic factors in experimentation were found as in their typically developing peers, namely nonverbal reasoning and grammar. The results suggest that kindergartners with learning problems show a developmental delay in experimentation. Instructional methods for children with learning problems should take these individual differences and developmental delay into account. An important conclusion is that kindergartners with learning problems can design multivariable experiments.